2015
DOI: 10.31887/dcns.2015.17.2/nmavrides
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of affective disorders in cardiac disease

Abstract: Patients with cardiovascular disease (CVD) commonly have syndromal major depression, and depression has been associated with an increased risk of morbidity and mortality. Prevalence of depression is between 17% and 47% in CVD patients. Pharmacologic and psychotherapeutic interventions have long been studied, and in general are safe and somewhat efficacious in decreasing depressive symptoms in patients with CVD. The impact on cardiac outcomes remains unclear. The evidence from randomized controlled clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 75 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Treatment of depression in cardiac patients reduces cardiac disease symptoms, morbidity, and disabilities (Mavrides & Nemeroff, 2015;Pedersen, von Känel, Tully, & Denollet, 2017), so it is important to monitor CHD patients, in particular, CHD patients with increasing NYHA class, to identify psychological distress. In such cases, the optimization of the medical treatment, inclusion in rehabilitation programs (Martínez-Quintana, Miranda-Calderín, Ugarte-Lopetegui, & Rodríguez-González, 2010), the promotion of physical activity and enabling psychological or psychiatric assessment (Sandberg et al, 2015) may be useful.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of depression in cardiac patients reduces cardiac disease symptoms, morbidity, and disabilities (Mavrides & Nemeroff, 2015;Pedersen, von Känel, Tully, & Denollet, 2017), so it is important to monitor CHD patients, in particular, CHD patients with increasing NYHA class, to identify psychological distress. In such cases, the optimization of the medical treatment, inclusion in rehabilitation programs (Martínez-Quintana, Miranda-Calderín, Ugarte-Lopetegui, & Rodríguez-González, 2010), the promotion of physical activity and enabling psychological or psychiatric assessment (Sandberg et al, 2015) may be useful.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, with the aid of Hospital Anxiety and Depression Scale (HADS), 7.3% of post-AMI patients showed moderate to severe depression at the three-month mark [20]. Similarly, Mavrides 2022 reported that 17-47 % depression were observed in CVD patients during his research work [4]. Women have high prevalence rate of depression after menopause as compare to general population [5].…”
Section: Introductionmentioning
confidence: 97%